(untitled) (Journal of Engineering, 2025)
Gypseous soil is classified as problematic soil, characterised by its characterized by complicated and erratic behavior, and is mostly found in arid and semi-arid areas of the globe. As for Iraq. Gypseous soils cover about 30-35% of the total area of Iraq, as this type of soil is found in the Western Desert and extends to the southern parts of the country. Gypseous soils are considered strong but susceptible to sudden collapse when wet. To control the collapse of gypsum soils, Geotextiles are among the most popular kind of geosynthetic material used for soil reinforcement. The goal of this study is to determine whether woven geotextiles can improve the ultimate bearing capacity of foundations constructed on gypsum soil. The foundation is built from a strong 10mm thick steel plate measuring 100mm x 100mm. In this study, the depth of the geotextile layer that was placed at depths of (0.1B, 0.2B, 0.4B, 0.8B, B) was determined from the width of the foundation used, the number of layers of the reinforcement material (one layer, two layers, and three layers), and the layer-to-layer vertical spacing. Geotextiles: The geotextiles’ breadth was also examined. The trials’ findings demonstrated that adding geotextile reinforcement to soil can help it have a higher bearing capacity. and reduce the settlement of the gypsum soil. It was found that placing geotextiles at depths of (0.8B-B) is the best depth chosen, and the results were also revealed. The test showed that using three layers of geotextile gave positive results. Additionally, the test findings demonstrated that the reinforcement’s composition had a significant impact on the behavior of the foundation